2020
DOI: 10.1038/s41467-020-19415-3
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of multiple anti-CRISPRs highlights anti-defense gene clustering in mobile genetic elements

Abstract: Many prokaryotes employ CRISPR–Cas systems to combat invading mobile genetic elements (MGEs). In response, some MGEs have developed strategies to bypass immunity, including anti-CRISPR (Acr) proteins; yet the diversity, distribution and spectrum of activity of this immune evasion strategy remain largely unknown. Here, we report the discovery of new Acrs by assaying candidate genes adjacent to a conserved Acr-associated (Aca) gene, aca5, against a panel of six type I systems: I–F (Pseudomonas, Pectobacterium, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 83 publications
(87 reference statements)
5
89
2
Order By: Relevance
“…As an example, it was recently shown that AcrIF11 inactivates Csy by specifically ADP-ribosylating a key residue in the PAM-recognition loop, thereby inhibiting DNA binding ( 47 ). The discovery of an additional 10 AcrIF inhibitors (AcrIF15–24) ( 17 ) presents another interesting case as these newly discovered inhibitors may fall within one of the previously described methods of inhibition or lead to the discovery of new mechanisms against type I-F CRISPR–Cas systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, it was recently shown that AcrIF11 inactivates Csy by specifically ADP-ribosylating a key residue in the PAM-recognition loop, thereby inhibiting DNA binding ( 47 ). The discovery of an additional 10 AcrIF inhibitors (AcrIF15–24) ( 17 ) presents another interesting case as these newly discovered inhibitors may fall within one of the previously described methods of inhibition or lead to the discovery of new mechanisms against type I-F CRISPR–Cas systems.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, nine additional AcrIF families (AcrIF6–14) were reported ( 14–16 ). Recently, more AcrIF inhibitors have been found that extend to AcrIF24 ( 17 ). The Csy complex is composed of four Cas proteins including Cas5f, Cas6f, Cas7f and Cas8f in a stoichiometry of 1:1:6:1, and a 60-nt crRNA that integrates all these protein subunits ( 18–22 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the enterobacteria P2-like phages harbor a large set of different genes at the Z/fun locus (33) thought to affect virulence. Anti-defense genes have also been found in diversity hotspots in phage genomes (34,35).…”
Section: Introductionmentioning
confidence: 99%
“…It was pro posed that similar to the defense islands, anti defense genes tend to form clusters in phage genomes or mobile genetic elements. Existence of such anti defense islands should promote discovery of novel host defense inhibitors [47]. Viral counter defense systems are beyond the scope of the current paper, and this subject can be further explored in other reviews [ 48 50].…”
Section: Introductionmentioning
confidence: 99%